Israel defence forces manpower in its early years - Neemani, Elad (Sodobni vojaški izzivi, 2018)
This article examines the evolution of the manpower crisis in the Israel Defence Forces (IDF) during the Israeli War of Independence and in the early years of the state. It aims to widen the understanding of the IDF%s organizational and social problems by describing them as a post-colonial, overriding strategic crisis that affected all army units. Recent research studies have focused on parts of the issue, concentrating mainly on themes related to the field of operations. This article wishes to add to those studies by describing the main characteristics and boundaries of the crisis. Understanding the Israeli case will contribute to our knowledge of the ways post-colonial armies are formed, and their ways of coping with their social diversity.
Keywords: civil-military; civilno-vojaški odnosi; crisis; Israel; Izrael; izraelska vojska; kriza; manpower; popolnjenost; post-colonial; postkolonialno obdobje; pridobivanje kadra; recruitment; retention; zadrževanje kadra